Investigation of compressible fluid behaviour in a vent pipe during blowdown - Rajiwate, Farhan Liyakat Husain (Curtin University, 2011)
In the process industry, upset conditions can result in the release of fluids to the atmosphere. Such a release process is known as ‘Blowdown’. Accurate modeling and prediction of the blowdown process is important in determining the consequences of venting operations and the design conditions required for vent and flare systems. The predicted information such as the rate at which the fluids are released, the total quantity of fluids released and the physical state of the fluid is valuable and helps in evaluating the new process designs, process improvements and improves the safety of the existing processes.Blowdown events, amongst other transient processes, are the subject of particular interest to the chemical, oil/gas, and power industries. In the process plants, particularly in the hydrocarbon industry, there are many large vessels and pipelines operating under pressure and containing hydrocarbon mixture. Depressurization of such equipment’s is frequently necessary during maintenance, and in an emergency it may have to be rapid. Hazards arise because of the very low temperatures generated within the fluid during the process and also from the large total efflux and high efflux rates that arise from the large inventory of the long pipelines and high pressure vessels. This inevitably leads to a reduction in the temperature of the vessel / pipeline and associated vent system, possibly to a temperature below the ductile-brittle transition temperature of the material from which the vessel, pipeline or piping is fabricated. To date, a number of blowdown models and simulation codes related to pressure vessels and pipelines have been developed to estimate the blowdown conditions in pressure vessels and pipelines. There is no general model developed specifically for analyzing the conditions developed in a vent pipe.The scope of this work encompasses investigating the behavior of compressible gas in a vent pipe, during venting, by developing a vent pipe model. A fluid dynamic and thermodynamic approach is used in developing the model. The investigation is focused on the pressure, temperature and flow rates of flowing gas and pipe wall temperatures. The model is validated with experimental data generated by performing steady-state venting runs using compressed air. The model is also validated by comparing the simulations performed in Aspen Hysys for single component gases such as air, carbon dioxide, methane and multicomponent gases which are in very close agreement.